A Conceptual Design of Solar-Powered Water Surface Garbage Cleaning Robot - Tatar, Ahmet B.; Tanyildizi, Alper K.; Tasar, Beyda (Institute of Electrical and Electronics Engineers Inc., 2023)
Today, marine organisms are damaged due to increasing marine pollution, and chemical/biological deterioration in wastes can lead to the formation and spread of infectious diseases. For this reason, many above and below-water garbage-cleaning robots have been designed in order to reduce the negative effects of pollution on rivers, lakes, and oceans. Within the scope of this study, all these designs were analyzed and a three-dimensional concept design of a low-cost, lightweight surface-mounted garbage collection robot was made in the SolidWorks environment and presented. The designed robot will be able to produce its own motion energy with the light solar panels that will be placed on it. © 2023 IEEE.
4th International Conference on Artificial Intelligence, Robotics and Control, AIRC 2023 -- 9 May 2023 through 11 May 2023 -- Cairo -- 194264
Keywords: cleaning robot; garbage; solar powered; water surface